Collaborative Waste Management Initiatives with Local Communities in Sidamukti Village, Pandeglang, Banten - Nurhaida, Dida; Binartha, Ciptadhi Tri Oka; Effendi, Harris; Busnetty, Ida; Ischak, Mohammad; Maulani, Mustamina; Kurniawan, Wawan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Global waste generation continues to intensify environmental pollution and contribute to climate change, with municipal solid waste projected to increase substantially by 2050. In Indonesia, rapid urbanization has resulted in approximately eight million tons of waste produced daily in major cities, highlighting the urgent need for improved waste management systems and greater public awareness. In Banten Province – particularly in Sidamukti Village, a coastal area in Pandeglang Regency – these challenges are further exacerbated by insufficient waste management practices. To address these issues, Universitas Trisakti implemented a Community Service Program (PKM) in Sidamukti Village aimed at strengthening waste management practices and increasing community knowledge of health and hygiene. Program activities included health and hygiene (PHBS) awareness sessions, shell-craft training, eco-enzyme production, composting, and the establishment of a waste bank. The methods employed consisted of workshops, hands-on training, and community engagement activities. A paired-sample t-test was used to assess the effectiveness of the interventions. The results showed significant improvements in PHBS practices as well as in participants’ skills in crafting, eco-enzyme production, composting, and waste bank management. These findings demonstrate the effectiveness of the PKM initiative in enhancing community-based waste management and promoting environmentally responsible practices.